Prediksi Jumlah Calon Siswa Baru Menggunakan Metode Double Exponential Smoothing Brown (Studi Kasus: SMK Ma’arif NU 1 Purwokerto Tahun Pelajaran 2024/2025) - Nurohmah, Siti; Kartika, Dwiani Listya; Muhassanah, Nuraini; Yuniarti, Dwi Ariani Finda (UIN Walisongo Semarang, 2024)
The number of new students registering at SMK Ma'arif NU 1 Purwokerto from 2010 to 2023 has increased and decreased. This fluctuating pattern is a problem faced in determining strategies to attract new students to register. Large fluctuations in student numbers can cause instability in school revenues, which affects all operational aspects and will impact the school's reputation in the eyes of the community and prospective students. In this regard, it is necessary to take action, namely forecasting the number of new students registering for the 2024/2025 academic year. The aim of this research is to determine the prediction of the number of prospective new students at SMK Ma'arif NU 1 Purwokerto using theDouble Exponential Smoothing Brown in the 2024/2025 academic year. From the research results, it was obtained that the number of new students in the 2024/2025 academic year was based on overall data on students who registered with the best α parameter α = 0.2 with a value ofMAD = 6,02, MSE = 68,37, andMAP= 20.23%, namely 42 students. The forecast for the number of new students registering at SMK Ma'arif NU 1 Purwokerto based on overall data from the school has increased from the previous year. Value resultsMAPshows that the forecasting that has been carried out falls into the category of adequate forecasting method capabilities so that it can be used to predict the number of new students enrolling at SMK Ma'arif NU 1 Purwoketo and the predicted value for the following year can be known.Keywords: predictions, forecasting, new students, Double Exponential Smoothing Brown